The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1987
DOI: 10.1002/ajmg.1320270204
|View full text |Cite
|
Sign up to set email alerts
|

Isochromosome 12p mosaicism (Pallister mosaic aneuploidy or Pallister‐Killian syndrome): Report of 11 cases

Abstract: We report on 11 cases of isochromosome 12p mosaicism (or Pallister mosaic aneuploidy syndrome) in which the isochromosome is usually absent in cultured lymphocytes but present in fibroblasts. The patients range in age from a 22-week-gestation fetus to a 45-year-old man. They have a distinct pattern of anomalies which enables one to make a diagnosis based on clinical manifestations alone. Craniofacial manifestations include "coarse" face with prominent forehead, sparsity of scalp hair, hypertelorism, epicanthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
2

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 13 publications
5
99
2
Order By: Relevance
“…The distinct phenotype of PKS enables a diagnosis based solely on clinical manifestations in the majority of cases. 3,7 In our patient, the clinical findings were consistent with PKS. Nevertheless, cytogenetic analysis did not reveal the typical finding of supernumerary i(12p) in fibroblasts.…”
Section: Discussionsupporting
confidence: 75%
“…The distinct phenotype of PKS enables a diagnosis based solely on clinical manifestations in the majority of cases. 3,7 In our patient, the clinical findings were consistent with PKS. Nevertheless, cytogenetic analysis did not reveal the typical finding of supernumerary i(12p) in fibroblasts.…”
Section: Discussionsupporting
confidence: 75%
“…In a number of cases (Lopes et al, 1985;Raffel et al, 1986;Pauli et aI., 1987;Reynolds et al, 1987;Warburton et al, 1987), i(12p) was found in 10-20~ of blood lymphocytes. The percentage of tetrasomy 12p in lymphocytes in our case (43~) was even higher.…”
Section: Discussionmentioning
confidence: 93%
“…It should be noted that tetrasomy 12p mosaicism has been increasingly ascertained at birth or by prenatal diagnosis. Review of autopsy findings in 8 such cases (Gilgenkrantz et aI., 1985;Lopes et al, 1985;Hiraishi et aI., 1987;Pauli et al, 1987;Reynolds et al, 1987;Steinbach and Rehder, 1987;Warburton et al, 1987) showed that internal malformations are not at all rare and lung hypoplasia is a common pathological finding (Table 4). This type of malformation may explain why neonatal asphyxia is frequently associated with Pallister-Killian syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This syndrome (also known as Pallister mosaic aneuploidy syndrome or isochromosome 12p mosaicism) is characterized by postnatal growth retardation, seizures, hypotonia, deafness, profound mental retardation, minimal speech development, and a distinctive facial appearance (high prominent forehead, ocular hypertelorism, sparse anterior scalp hair, prominent lower lip, large ears with thick protruding lobules, cupid-bow shaped upper lip, and a long philtrum) [Pallister et al, 1977;Teschler-Nicola and Killian, 1981;Reynolds et al, 1987;Bergoffen et al, 1993]. A chromosome 12 abnormality (tetrasomy 12p) has been reported in skin biopsies from these patients but this chromosome anomaly is usually not found (or in only a small proportion, e.g., <0.5%, of blood cells) in peripheral blood [Raffel et al, 1986;Warburton et al, 1987;Larramendy et al, 1993;Ohashi et al, 1993].…”
Section: To the Editormentioning
confidence: 99%